The relationship between meniscal tear and neuropathic pain in patients with knee pain (Annals of Medical Research, 2021)
Aim: To determine whether the presence of meniscal tear, bone marrow edema, synovitis and effusions in the knee joint present a risk factor for neuropathic pain.Material and Methods: A total of 103 patients (66 females, 37 males) with knee pain were included in the study. Meniscal tear, bone marrow edema, effusion and synovitis in the knee joint were determined using magnetic resonance imaging. The neuropathic pain level of the patients were evaluated according to the Leeds Assessment of Neuropathic Symptoms & Signs (LANSS). The visual analogue scale (VAS) used for the evaluation of pain. Results: Neuropathic pain was found in 14.6% of patients according to the LANSS scale. Night pain was higher in patients with neuropathic pain compared with those without neuropathic pain (P=0.014). Rest pain was higher in patients with neuropathic pain compared with those without neuropathic pain (P=0.026).Movement pain was higher in patients with neuropathic pain compared to those without neuropathic pain (P=0.004).Meniscal tear was present in 76.7% of the patients. Neuropathic pain was identified in 16.45% of meniscal tears, and the ratios of bone marrow edema, synovitis and effusion were 22.3%, 43.7% and 64.1%, respectively. The relative risk ratios of meniscal tear, bone marrow edema, effusion in the knee and synovitis in the development of neuropathic pain (with 95% confidence interval) were 1.9 (0.4–8.1), 0.9 (0.3–2.8), 0.8 (0.3–2.2) and 0.5 (0.2–1.4), respectivelyConclusion: Based on our study findings, meniscal tears, bone marrow edema, knee effusion and synovitis lesions did not have an effect on neuropathic pain development.Keywords: Neuropathic pain; meniscal tear; bone marrow edema; synovitis; effusion.
Keywords: Neuropathic pain; meniscal tear; bone marrow edema; synovitis; effusion.